Pretreatment of Lignocelollusic Biomass Based on Improving Enzymatic Hydrolysis - Madadi, Meysam; Tu, Yuanyuan; Abbas, Aqleem (International Journal of Applied Sciences and Biotechnology, 2017)
Lignocellulosic materials among the alternative energy resources are the most desirable resources that can be employed to produce cellulosic ethanol, but this materials due to physical and chemical structure arranges strong native recalcitrance and results in low yield of ethanol. Then, a proper pre-treatment method is required to overcome this challenge. Until now, different pre-treatment technologies have been established to enhance lignocellulosic digestibility. This paper widely describes the structure of lignocellulosic biomass and effective parameters in pre-treatment of lignocelluloses, such as cellulose crystallinity, accessible surface area, and protection by lignin and hemicellulose. In addition, an overview about the most important pre-treatment processes include physical, chemical, and biological are provided. Finally, we described about the inhibitors enzymes which produced from sugar degradation during pre-treatment process and the ways to control this inhibitors. Int. J. Appl. Sci. Biotechnol. Vol 5(1): 1-11